2018
DOI: 10.1038/s41388-018-0309-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived exosomes promote tumor self-seeding in hepatocellular carcinoma by transferring miRNA-25-5p to enhance cell motility

Abstract: Tumor self-seeding occurs when circulating malignant cells reinfiltrate the original tumor. The process may breed more aggressive tumor cells, which may contribute to cancer progression. In this study, we observed tumor self-seeding in mouse xenograft models of hepatocellular carcinoma (HCC) for the first time. We confirmed that circulating tumor cell uptake of tumor-derived exosomes, which are increasingly recognized as key instigators of cancer progression by facilitating cell-cell communication, promoted tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Previous studies have reported that cancer cells secrete exosomes in great amounts and transfer cancer-associated signaling molecules to surrounding cells [ 23 ]. Post-transcriptional gene expression in recipient cells can be regulated by microRNAs contained in exosomes [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that cancer cells secrete exosomes in great amounts and transfer cancer-associated signaling molecules to surrounding cells [ 23 ]. Post-transcriptional gene expression in recipient cells can be regulated by microRNAs contained in exosomes [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Circulating exosomes could be released into the extracellular environment through the fusion of multivesicular bodies approach with the membrane of certain body fluid such a serum or plasma. 12 Exosome-derived non-coding RNAs (ncRNAs) have been proved with different expression profiles which could indicate the characteristics of a certain tumour, or their function in tumour progression and metastasis. 12 Exosome-derived non-coding RNAs (ncRNAs) have been proved with different expression profiles which could indicate the characteristics of a certain tumour, or their function in tumour progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…This exosomal miRNA, released by liver cancer cells, is able to attenuate the junction integrity of recipient endothelial cells (HUVEC) by targeting adhesion molecules such as VE-cad, p120, and zonula occludens 1 (ZO-1), thus increasing the vascular permeability both in vivo and in vitro [102]. The subsequent tumor cell transendothelial motility process is promoted by exosomal miR-25-5p [103]. The horizontal transfer of miR-25-5p between cancer cells induces migratory characteristics in recipient cells by targeting leucine rich repeat-containing 7 (LRRC7) protein.…”
Section: The Cellular Crosstalk In the Tumor Microenvironment Promotementioning
confidence: 99%
“…The horizontal transfer of miR-25-5p between cancer cells induces migratory characteristics in recipient cells by targeting leucine rich repeat-containing 7 (LRRC7) protein. LRRC7, also known as densin-180, is a transmembrane protein that binds and stabilizes cell motility proteins such as δ-catenin and N-cadherin, ZO-1, Ca2+/calmodulin-dependent protein kinase II, and α-actinin [103]. LCRR7 downregulation by exosomal miR-25-5p transfer results in cell migration and tumor self-seeding in different sites.…”
Section: The Cellular Crosstalk In the Tumor Microenvironment Promotementioning
confidence: 99%